CHARACTERISTICS OF HEART FUNCTIONAL DISORDERS IN GOUT DISEASE - Toirov Doston Rustamovich; Berdiyev Doniyor Khasanovich (Galaxy International Interdisciplinary Research Journal, 2022)
In our study, 88 patients (all male) were selected to examine the structural and functional status of the myocardium in patients with gout. EchoCG screening was performed in patients with gout (recurrent and chronic).ECG and EchoCG examinations revealed changes in the cardiovascular system in 82% of patients. Moreover, while LV hypertrophy was detected in 43% of patients, the presence of AH was noted in 62% of these patients. At the same time, an average of 70% of patients with EchoCG were diagnosed with the following types of valvular lesions: IVB thickening - 50% of cases, LV posterior wall thickening - 44%, LA hypertrophy - 36%, LVDD - 31.5%. Various disturbances in heart rhythm and conduction have also been reported, with a predominance of ventricular extra systoles. At the same time, the above changes have been found to be more common in chronic forms of the disease. By the way, in this study it was found that the development of cardiopathy is directly related to the concentration of uric acid, xanthine oxidase in the blood.